2013
DOI: 10.1007/s00774-013-0550-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the PTH2R gene is associated with age-related degenerative changes in the lumbar spine

Abstract: Variation in the PTH2R gene is associated with age-related degenerative changes in the lumbar spine. Link to publication Citation for published version (APA): Åkesson, K., Tenne, M., Gerdhem, P., Luthman, H., & McGuigan, F. (2015). Variation in the PTH2R gene is associated with age-related degenerative changes in the lumbar spine. Journal of Bone and Mineral Metabolism, 33(1), 9-15. DOI: 10.1007/s00774-013-0550-x General rights Copyright and moral rights for the publications made accessible in the public p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Also, TRPS1 contributes to osteoblast differentiation (Piscopo et al 2009). The parathyroid hormone-2 receptor (PTH2R) plays a role in the control of proliferation and differentiation of growth plate chondrocytes (Akesson et al 2015;Panda et al 2009). Variation in the PTH2R is associated with age-related vertebral degenerative changes (Akesson et al 2015) and may contribute to early-onset generalized OA (Meulenbelt et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also, TRPS1 contributes to osteoblast differentiation (Piscopo et al 2009). The parathyroid hormone-2 receptor (PTH2R) plays a role in the control of proliferation and differentiation of growth plate chondrocytes (Akesson et al 2015;Panda et al 2009). Variation in the PTH2R is associated with age-related vertebral degenerative changes (Akesson et al 2015) and may contribute to early-onset generalized OA (Meulenbelt et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, extensive genetic and genomic studies have conducted to discover genes/SNPs associated with BMD variation in human populations . However, our understanding about the underlying association mechanism is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, extensive genetic and genomic studies have conducted to discover genes/SNPs associated with BMD variation in human populations. [29][30][31][32][33][34] However, our understanding about the underlying association mechanism is very limited. Besides, a majority of phosSNPs in the GPS 2.0 database were predicted, and their potential effects on protein phosphorylation have not been validated by experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Parathyroid hormone (PTH) is a key regulator of calcium metabolism and contributes to skeletal development by regulating chondrocyte proliferation and differentiation during early bone growth 34 . Previous genetic studies have linked other PTH genes with age-related degenerative changes in lumbar spine 35 and BMD 20 . In this study, we identified a three-SNP haplotype (rs12425376-rs10843047-rs42294, P = 5.75 × 10 −6 ) that was significantly associated with the diagnosis of OP.…”
Section: Discussionmentioning
confidence: 99%